Determination of insoluble avian eggshell matrix proteins - Mikšík, Ivan; Sedláková, Pavla; Lacinová, Katerina; Pataridis, Statis; Eckhardt, Adam (Analytical and bioanalytical chemistry, 2010)
The organic components of bones and other mineralized tissues have a high impact on the organization and deposition of calcium, and consequently influence the mechanical properties of those tissues. The extractable proteins of avian eggshells have been studied extensively and many of them have been identified; insoluble (non-extractable) proteins have been sparsely studied, however. In the work discussed in this paper we studied EDTA-insoluble proteins by gradual decalcification of eggshell with EDTA. The insoluble proteinaceous films were chemically treated with cyanogen bromide and the mixtures of large fragments obtained were gradually precipitated with salt. The separated fractions were digested with trypsin and analyzed by HPLC-MS-MS (ion trap mass spectrometer). Analysis of the entire eggshell matrix (without precipitation steps) only enabled 6 proteins to be determined (ovocalyxins 32 and 36, ovocleidin 17 and 116, clusterin, and ovalbumin). Pretreatment of the individual eggshell layers and gradual precipitation with salt markedly increased the number of proteins identified - 28 proteins were determined. We identified for the first time collagens I (two chains) and III in the eggshell matrix, and Kunitz-like protease inhibitor as a major shell matrix protein. Besides the above mentioned proteins we can also mention EDIL3, fibronectin, sulfhydryl oxidase, tubulin alpha 1, lysozyme, Dickkopf-related protein 3, keratins, and ovotransferrin. The relative abundances of proteins in all eggshell layers were determined using the exponentially modified protein abundance index (emPAI). In the cuticle layer seven proteins were identified, whereas 16 proteins were described in the palisade layer and 23 in the mammillary layer.
Keywords: kur domácí; Animals; vysokoúčinná kapalinová chromatografie; Egg Shell; vaječná skořápka; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, High Pressure Liquid; zvířata; Egg Proteins; Chickens; Solubility; Spectrometry, Mass, Electrospray Ionization; vaječné proteiny; rozpustnost